BREEDING SITES UTILIZED BY ANOPHELES MOSQUITOES IN KATSINA STATE, NIGERIA - Umar, Aliyu; Kogi, E. (FUDMA Journal of Sciences, 2023)
The transmission of malaria and the development of the Anopheles vector are directly linked to the breeding sites. Consequently, the breeding sites of Anopheles in Katsina State were determined during dry and wet seasons. To locate larval habitats, each sampling location was screened systematically within a 1Km radius and all water collections containing larvae were tagged, and subsequently drawn on a map using Arcicad software.An. gambiae were the most preponderant in pools with 332 (20.13%) and least abundance were 120 (7.28%) in overhead tanks. There was no significant difference (p >0.05, F=9.28) between pool and pond nor between concrete reservoir and overhead tank in terms of collected larvae. Anopheles larvae were found in water bodies that ranged in size between 12 cm for e.g. rain pools to 50 m for earth dams. Anopheles were found breeding in association with vegetation in the water bodies, e.g. Typha species (Typha angustifolia) and water lilies (Nyrnphaea spp.) and rotten vegetation. Some of the observed ponds were permanent because they contain water throughout the year while others were temporary because they dried off during dry season between March and April of every study year from 2009 to 2014. The observed water bodies that were clean include rain pools while other pools were contaminated with oil, feaces, waste water, sewage etc. Others were polluted with organic matter, algal growth, decaying plant, animal waste etc. Habitats like earth dams and broken plastic reservoirs were completely exposed to sunshine however domestic water containers like buckets were only